Difference in the regulation of IL-8 expression induced by uropathogenic E. coli between two kinds of urinary tract epithelial cells - Chen Chun-Ming (Journal of Biomedical Science, 2009)
Abstract Bacterial adherence to epithelial cells is a key virulence trait of pathogenic bacteria. The type 1 fimbriae and the P-fimbriae of uropathogenic Escherichia coli (UPEC) have both been described to be important for the establishment of urinary tract infections (UTI). To explore the interactions between the host and bacterium responsible for the different environments of UPEC invasion, we examined the effect of pH and osmolarity on UPEC strain J96 fimbrial expression, and subsequent J96-induced interleukin-8 (IL-8) expression in different uroepithelial cells. The J96 strain grown in high pH with low osmolarity condition was favorable for the expression of type 1 fimbriae; whereas J96 grown in low pH with high osmolarity condition was beneficial for P fimbriae expression. Type 1 fimbriated J96 specifically invaded bladder 5637 epithelial cells and induced IL-8 expression. On the contrary, P fimbriated J96 invaded renal 786-O epithelial cells and induced IL-8 expression effectively. Type 1 fimbriated J96-induced IL-8 induction involved the p38, as well as ERK, JNK pathways, which leads to AP-1-mediated gene expression. P fimbriated J96-induced augmentation of IL-8 expression mainly involved p38-mediated AP-1 and NF-κB transcriptional activation. These results indicate that different expression of fimbriae in J96 trigger differential IL-8 gene regulation pathways in different uroepithelial cells.